Analizar los efectos de la implementación de las NIIF sección 13 (inventarios para pymes) vs PCG (2019)
This document takes as a purpose to find the similarities and the differences in the countable procedures for the identical inventories to the beginning generally accepted in Colombia and the established ones by the international norm of financial information for pymes in the section thirteen, for which there is born in mind the initial recognition, the methods of later valuation and the information to be revealed. With regard to the methodological aspects, the work is based on an investigation of descriptive type. The investigation design includes documentary and not experimental elements. The deductive method has been selected. The used approach corresponds to the qualitative one. In the analysis of the results there will be able to be the determinant reasons of the convergence or difference between the national normative and the international norms of financial information for the inventories; which is supported by the development of an exercise raised by the author